Products and Mechanism of the Reactions of OH Radicals and Cl Atoms with Methyl Methacrylate (CH2═C(CH3)C(O)OCH3) in the Presence of NOx - Blanco, Maria Belen (2014)
The OH radical and Cl atom initiated photodegradation of methyl methacrylate has been investigated in a 1080 L quartz-glass environmental chamber at 298 ± 2 K and atmospheric pressure of synthetic air using in situ FTIR spectroscopy to monitor the reactants and products. The major products observed in the OH reaction were methyl pyruvate (92 ± 16%) together with formaldehyde (87 ± 12%) as a coproduct from the C1–C2 bond cleavage channel of the intermediate 1,2-hydroxyalkoxy radical, formed by the addition of OH to the terminal carbon of the double bond which is designated C1. For the Cl atom reaction, the products identified were chloroacetone (41 ± 6%) together with its coproduct formaldehyde (35 ± 5%) and methyl pyruvate (24 ± 4%) together with its coproduct formylchloride (25 ± 4%). The results show that the fate of the intermediate 1,2-chloroalkoxy radical involves not only cleavage of the C1–C2 bond but also quite substantial cleavage of the C2–C3 bond. The present results are compared with previous studies of acrylates, showing different branching ratios for the OH and Cl addition reactions in the presence of NOx. Atmospheric implications are discussed.